Chemical Properties of Bogor Local Palm Sugar from Leuwiliang and South Bogor and Its Utilization on Physical and Preference Properties of Cuko Pempek - Agustiani, Novi; Aminullah, Aminullah; Rohmayanti, Titi (JURNAL AGROINDUSTRI HALAL, 2025)
Cuko pempek is a palm sugar sauce with sour taste and a distinctive pungent aroma. The objective were to obtain palm sugar characteristics, and to study the effect of palm sugar types and water addition on the preference, viscosity, and total dissolved solids (TDS) of cuko. The preliminary research was to obtain chemical composition of palm sugar and spiciness preference for cuko with several chili concentration. The primary research used completely randomized design with two factors of palm sugar types and sugar to water ratio. The preliminary showed 5% chili was the most preferred spiciness, as well as the chemicals of Palembang palm sugar met the standard, while ash content of local palm sugar of Leuwiliang and South Bogor exceeds the SNI standard. Leuwiliang palm sugar has the highest ash and sucrose content, while Palembang palm sugar has the highest reducing sugar. The primary results showed that different palm sugar significantly affected the taste preference and the viscosity of cuko. Water addition could reduce the thickness and overall preferences, as well as the TDS and the viscosity of cuko. Also, Bogor local palm sugar could be used as raw material in cuko pempek as well as Palembang palm sugar, where the chosen in this study was South Bogor palm sugar with sugar and water ratio of 1:2.